DAMPAK APLIKASI CHATGPT TERHADAP DUNIA USAHA - RAYYAN SUGANGGA; INTAN PERMATA SARI; BIMA TEGUH WIJAYANTO (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2023)
The use of ChatGPT is increasingly widespread, including in the business world. ChatGPT like technology in general has 2 sides, namely positive and negative sides. This article intends to examine more deeply the potential benefits of ChatGPT in the business world including its negative impacts and risk mitigation. This article is in the form of a critical review of the ChatGPT Application by conducting application user experience testing and literature studies. From this research it can be found that ChatGPT does bring benefits, but also carries negative risks for workers or humans in general, so risk mitigation needs to be prepared such as increasing skills, wisdom and critical thinking.